Evaluation of Topical Formulation based on Ceramides and Study of its Effect on the Skin Barrier Properties - Castro, Filipa Alexandra Pires de (2023)
This work is divided into three chapters. The first chapter refers to the research work in Pharmaceutical Sciences, developed under the ERASMUS+ program in the Skin Barrier Research Group of the Faculty of Pharmacy of Charles University. The second chapter reports my experience in hospital pharmacy at the Centro Hospitalar Universitário da Cova da Beira. Finally, the third chapter describes my experience in community pharmacy at Farmácia Silveira Mem Martins. The first chapter is entitled “Evaluation of topical formulation based on ceramides and study of its effect on the skin barrier properties” and was carried out within the scope of the research component, under the supervision of Prof. Dr. Andrej Kovacik. It is known that changes in the lipid content of the stratum corneum, especially ceramides, correlate with skin diseases. The present work aimed to study the role of topical formulations based on ceramides and the barrier properties of the skin after applying the prepared emulsions. The study concluded that the topical application did not favor the barrier properties, however, it increased the organization of the lipid chain. These results may be useful to further support other studies that develop topical lipid-based formulations. In the second chapter, I report my experience over 8 weeks in Hospital Pharmacy, under the guidance of Dra. Olímpia Fonseca. In this chapter, I present everything I have learned about the medication circuit in the hospital and how the pharmacist plays a key role in its multidisciplinary team. In the third chapter, I describe my experience in Community Pharmacy, under the guidance of Dra. Bruna Castanheira. I described the activities to be developed in the community pharmacy and how the pharmacist has an active role in society.